1980
DOI: 10.1093/ajcn/33.2.227
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the dietary intakes of copper, iron, manganese, and zinc on the trace element content of human milk

Abstract: Fifteeen breast-feeding mothers who volunteered for a study of trace elements in human milk, kept two 7-day food records during the course of lactation. The 1st survey week ranged from 6 to 8 weeks and the 2nd survey week from 17 to 22 weeks postpartum. The milk samples submitted for analysis represented a sample of every feed during a period of 24 hr and contained foremilk and hindmilk in equal proportions. The 7-day food records were handled by a computing system to give an average daily food consumption and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
50
4

Year Published

1982
1982
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(63 citation statements)
references
References 7 publications
9
50
4
Order By: Relevance
“…About 75 mg of elemental Cu is needed daily to meet the requirements of pregnancy and the calculated daily Cu accumulation by a fetus is 51 mg/kg body weight/24 h and at term (Gathwala and Vadav, 2002). So, the relatively low serum Cu concentrations, which were evaluated in the Albanian mothers, in whom Cu intake was very poor, as indicated from their dietetic diaries, could be responsible for the low Cu concentrations of their infants (Vuori et al, 1980;Agget, 1994;Thomas, 2001). Albanian immigrant mothers live under difficult low socioeconomic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…About 75 mg of elemental Cu is needed daily to meet the requirements of pregnancy and the calculated daily Cu accumulation by a fetus is 51 mg/kg body weight/24 h and at term (Gathwala and Vadav, 2002). So, the relatively low serum Cu concentrations, which were evaluated in the Albanian mothers, in whom Cu intake was very poor, as indicated from their dietetic diaries, could be responsible for the low Cu concentrations of their infants (Vuori et al, 1980;Agget, 1994;Thomas, 2001). Albanian immigrant mothers live under difficult low socioeconomic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have indicated that maternal dietary zinc intake does not in¯uence concentrations in milk (Feeley et al, 1983;Vuori et al, 1980). However, in many studies involving supplementation of the diet, a large number of women abandoned the project before ®nishing the supplementation period.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, 3 of 64 cases had the levels of hair zinc content below 100 µg/ g which will be implicated as zinc deficiency (Committee on Nutrition 1978), and the milk zinc levels in these cases were the lowest levels of the tested samples. It was shown that the amount of daily zinc intake did not affect the zinc content of breast milk (Karmarkar and Ramakrishman 1960;Vuori et al 1980), while in animal experiments, milk zinc content can be raised by increasing the zinc intake (Underwood 1971a, b). Thus, supplementation of zinc to maternal diet seemed to be useful in lactating women, especially in cases with zinc deficiency.…”
Section: Discussionmentioning
confidence: 99%